Al-Quran Education Park Teacher Learning Model in Supporting Student Achievement - Teguh Saputra, Muhammad (Devotion : Journal of Community Service, 2021)
This study aims to find out what kind of learning model is used by the teachers of Taman Pendidikan Al-Quran Musholla Darussalam from time to time, which is explained by analyzing: (1) what learning paradigm is used, (2) what learning theory and methods are applied, (3) and what activities are carried out. This research is important to describe because it raises the learning strategies carried out in research from time to time, so that they are relevant to the problems of the times that require teachers to quickly adapt to the dynamic development of science and technology. The method used in this research is qualitative in the form of field research. The results used are: (1) the paradigm used shifts from teacher-centered to student-centered (2) the theory used consistently uses behavioristic theory and the dominant method used is the demo method (3) the activities carried out include; (a) reading iqra and quran books; (b) summarize books on Islamic creed and the history of Islamic culture; (c) memorizing the quran and hadith, and so on.